Assessing and improving countries' logistics skills and training - Alan C. McKinnon; Kai Hoberg; Moritz Petersen; Christina Busch (Digitalization in Maritime and Sustainable Logistics: City Logistics, Port Logistics and Sustainable Supply Chain Management in the Digital Age. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 24, 2017)
Evidence is mounting to suggest that there is a global shortage of people with the right skills to meet the evolving needs of the logistics industry. Especially emerging regions are lagging behind, inhibiting economic growth. Thus, governments should systematically assess and address skills shortages in logistics. Commissioned by the World Bank, we devised a toolkit for assessing the availability of logistics skills within low- and middle-income countries. We built on the maturity model concept and embedded it into an assessment and policy recommendation process. An international panel of logistics training experts provided advice on the toolkit development. The toolkit allows government officials and staff from international organizations to gain a quick but comprehensive overview of the logistics skills and training situation in a particular country. A pilot study done in Togo demonstrated the toolkit's relevance and practicality. The toolkit is the first of its type to help governments undertake a systematic analysis of logistics skills and training at the macro level. Previous research in this area takes a micro-level perspective focusing on the logistics workforce of individual companies.
urn:nbn:de:gbv:830-88217791; 10419/209193; https://econpapers.repec.org/RePEc:zbw:hiclpr:24
Keywords: 650; logistics; skills shortage; competences; maturity model